Au fil du temps (1976) ou la loi du seuil - Isabelle Singer (Conserveries Mémorielles)
By choosing to live in a truck, the heroes of Kings of the Road, a Wim Wenders film of 1976, have an exceptional experience of the threshold. They refuse to belong to a homeland and abandon the traditional idea of home. They travel along the split German territory through which runs a border that will remind them at every instant of the historical traumas. On the windshield of the truck, the outside (nameless countryside, abandoned cities…) and the inside interact. Kings of the Road questions the landscape and tries to recover the myths hidden in it. In this way, Wenders’ approach is similar to that of Anselm Kiefer. The German landscape provokes refusal because there is always more than what is visible: layers of guilt that the myth has covered. The choice of being a nomad is an anterior state of humanity, prior to the idea of a homeland. It is also the choice of loneliness as a refusal to uncover the myths. Belonging to the German territory is profoundly problematic as its Fathers are profoundly guilty. The history of cinema will work as a substitute to History itself. The main characters of the film are in search of a home in this land. On the road, cinema catches these beings on the threshold of hope.